Pengaruh Penambahan Serbuk Daun Kelor Terhadap Kadar Fe, Vitamin C, Dan Daya Terima Coklat Kelor (Kokoa Moringa Oleifera): Effect of Addition of Moringa Leaf Powder to Fe, Vitamin C, and Acceptability of Moringa Chocolate (Kokoa Moringa Oleifera) - Nurul Hidayah (Public Health and Safety International Journal, 2022)
Iron deficiency anemia is often experienced by adolescent girls. The Fe content in Moringa leaf powder and cocoa compounds is needed for the formation of hemoglobin, while the vitamin C content in Moringa can increase Fe absorption. Objective: to analyze the effect of adding Moringa leaf powder to the levels of Fe, Vitamin C, and the acceptability of Moringa chocolate. Methods: quasi-experimental research with Post Test Only Control Group Design. The proportion of addition of Moringa leaf powder to 100 g of compound chocolate is 0g, 10g, 20g, 30g. Statistical analysis of Fe and Vit C levels using the ANOVA test. The acceptability test sample was 25 students of the Ngawi regency government akper. Results: The results of the statistical test of Fe levels showed significant results, with a p value of 0.00 (p<0.05) The results of the statistical test of vitamin C showed significant results with a p-value of 0.00 (p<0.05).The results of the acceptability test showed that there was a significant difference between taste, color, texture, and aroma. Of the four Moringa chocolates, the most popular is the addition of 10g of Moringa leaf powder. Conclusion: this Moringa chocolate can meet the RDA for adolescents aged 16-18 years, with a daily iron requirement of 24 mg, and a daily vitamin C requirement of 75 mg.